Public Perception of Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis-MBG) on TikTok: A Netnographic Study - Sri Riris Sugiyarti; Farco Siswiyanto Raharjo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
his study examines public perception of the Free Nutritious Meal Program (Makan Bergizi Gratis-MBG) as reflected in interactions on TikTok, addressing the gap between policy design and its implementation in practice. Specifically, it seeks to understand how the public evaluates the implementation of MBG based on George C. Edwards III’s policy implementation framework, which includes communication, resources, disposition, and bureaucratic structure. This research adopts an exploratory qualitative approach using netnography. Digital data were collected through online observation, scraping, and documentation, and analyzed using thematic analysis. The findings reveal a paradox in policy implementation as reflected in public perception. While the consistency of program communication and the visible commitment of government officials were positively perceived, substantial criticism emerged regarding resources and bureaucratic structure. Public responses highlighted inequalities in supply chain management that tend to disadvantage local micro, small, and medium enterprises (MSMEs). In addition, critical weaknesses in the supervision of Standard Operating Procedures (SOPs) were identified, culminating in a mass food poisoning incident in Kulon Progo. This study contributes to the literature on policy implementation and digital society by demonstrating how TikTok functions as a critical digital space. It not only serves as a platform for policy dissemination but also acts as a “digital judge” that can rapidly erode public trust when implementation failures occur. Therefore, the government is strongly recommended to strengthen regulations protecting local economies and improve quality control mechanisms to address these bureaucratic gaps.